Role of gonadal hormones on brain sexualisation - Barbarino, Antonino; De Marinis, Laura (Medicina e Morale, 2024)
It is now definitively established that the differentiation that leads to sexual dimorphism is not limited to the genital area but affects the entire individual. In particular, while knowledge of the dimorphism of the cerebral pole concerning the hypothalamic-pituitary-gonadal axis, which subtends, in its vast complex, functions and behaviours connected with reproductive activity, has become fairly clear thanks to recent studies, nothing has yet been definitively established concerning the sexualisation of other cerebral areas and in particular of the neocortex, which represents the part of the brain particularly involved in cognitive activities.